Human‐factors training for surgical trainees. (June 2014) - Jones, Mark; Howells, Nick; Mitchell, Steve; Burnand, Henry; Mutimer, Jon; Longman, Robert
Summary Background Shortcomings in non‐technical skills have frequently been shown to play a role in adverse events during surgery. Human‐factors training has an increasing role to play in enhancing patient safety and reducing medical errors. Programmes in non‐technical skills are promoted by the surgical Royal Colleges in the UK and Ireland, and are currently aimed at consultants, senior trainees and theatre teams. Since 2009, the Severn Postgraduate Deanery School of Surgery in the UK has developed a 1‐day human‐factors training course specifically designed for junior surgical trainees. Methods Analysis of post‐course feedback on self‐assessed confidence in the use of non‐technical skills was undertaken for all junior surgical trainees undertaking the course in 2012/13. Results Thirty‐three junior surgical trainees attended the 1‐day human‐factors training course. In all, 91 per cent of trainees reported that the course would change their practice. There was a statistically significant difference between the self‐assessed confidence of trainees in the use of all four categories of non‐technical skills (p ≤ 0.001) before and after the course. Discussion The Severn Deanery offers a compulsory human‐factors training course for surgeons at the start of their career. Given the importance of reducing human error, maintaining patient safety and the introduction of competency‐based training with an emphasis on simulation, human‐factors training has a vital place in surgical training, and is highly recommended to others involved in training junior surgical trainees.